DevOps and information technology service management: A problem management case study - Adriano, Daniel Maass (2021)
The use of DevOps is a predominant attribute of businesses engaged in the development and maintenance of Information Technology systems. Although literature exploring DevOps practices has expanded, there is still much unexplored territory on its operational ramifications. This is particularly observed when considering their potential impact on ITSM frameworks such as ITIL, which governs Operations. This research aims to establish how DevOps principles and practices can be applied to Problem Management, a core Service Management process. Specifically, it explores which DevOps practices may be used throughout the Problem lifecycle, as well as benefits which may result from them. An exploratory case study was carried out with the participation of Problem Managers operating in a DevOps environment. Three data collection methods were applied: Semi structured interviews, in which participants described their experience and insight in relation to DevOps and Problem Management; documental analysis and observation, where processes and workflows were examined; and a focus group exercise in which study outcomes were discussed and systematized. This research indicates that DevOps practices have varying degrees of significance for a Problem Management process. Practices associated with continuous planning and collaboration are prone to having greater significance in a Problem lifecycle, with the potential of enabling benefits such as quicker Problem identification, higher quality Root Cause Analysis, and improved resolution times. The novelty of insight gathered in this study benefits both academics, through its contribution to an expanding body of knowledge, and professionals, considering the practical and applicable nature of findings. Future work is also presented.